Analysis of Resilience and Workload Among Healthcare Workers in Disaster-Prone Areas: A Mixed-Methods Study of Occupational Epidemiology and Health Resource Management at Puskesmas Peusangan, Bireuen Regency - Aris Winandar; Rizkha Maulana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Healthcare workers in disaster-prone areas face unique occupational challenges that affect their resilience and workload. This study aimed to analyze the relationship between resilience levels and workload among healthcare workers at Puskesmas Peusangan, Bireuen Regency, Aceh Province, Indonesia. A mixed-methods approach with explanatory sequential design was employed, combining quantitative cross-sectional survey (n=87) with qualitative in-depth interviews (n=15). Resilience was measured using the Connor-Davidson Resilience Scale (CD-RISC-25) Indonesian version, while workload was assessed using the NASA Task Load Index (NASA-TLX). Quantitative data were analyzed using Spearman correlation and multiple linear regression, while qualitative data underwent thematic analysis. Results showed that 43.7% of respondents had moderate resilience levels, while 51.7% experienced high workload. A significant negative correlation was found between resilience and workload (r=-0.486, p<0.001). Regression analysis revealed that disaster experience, years of service, and social support significantly predicted resilience (R²=0.412, p<0.001). Qualitative findings identified four main themes: adaptive coping strategies, community bonding, resource constraints, and institutional support gaps. The study concludes that healthcare workers in disaster-prone areas require targeted interventions to enhance resilience and optimize workload management. Policy recommendations include implementing resilience training programs, improving staffing ratios, and establishing peer support systems.